Blessing in disguise - Snelling, Lauraine (Snelling, Lauraine. Red River of the North, 1999)
The Bjorklund family has received word that Augusta Bjorklund is on her way from Norway to join them in North Dakota. When the train arrives in the town of Blessing with no Augusta aboard, the worried family hopes she will be on the train in the morning. But only her trunk arrives, so Bridget Bjorklund insists that Hjelmer, Augusta's brother, go find her. Augusta, after discovering her intended bridegroom had married someone else, decided to leave her broken heart in Norway and start a new life in America helping her mother run her boardinghouse. But knowing no English, Augusta misunderstands a ticket agent's directions in St. Paul, Minnesota, and in the harried confusion, she boards the wrong train. When she arrives at the end of the line, she is met by a handsome young rancher, Kane Moyer, waiting for his Norwegian mail-order bride ...